Multiple Myxomas in Right Ventricle A Case Report of Carneys Syndrome (University Heart Journal, 2014)
No AbstractDOI: http://dx.doi.org/10.3329/uhj.v9i1.19515 University Heart Journal Vol. 9, No. 1, January 2013; 56-58